Electricity sector reform and promoting renewable energy generation - LEE, Yoonha (KDI School, 2016)
From 1980s, countries started to reform the structure of stated owned companies for more efficiency and productivity. Electricity market has been targeted the first privatised or liberalised industry among major utilities such as transportation or telecommunication in most countries. Many researches have conducted to analyse the phenomenon of this liberalisation and its impact on economy. Some say that in privatised energy sector, renewable energy is rarely promoted since it is considered as less cost effective than fossil fuel generation. However, under the present situation that sustainable energy use has been being important and renewable energy issue has been gradually progressed, it seems worthwhile that revealing the relationship between these two contradicting concepts. Based on panel regression analysis, this paper finds that electricity market liberalisation has significant impact on renewable electricity generation. This paper also suggests that most of energy related variables affect differently for different groups based on their income level.
Thesis(Master) --KDI School:Master of Development Policy,2016